Assistenzsysteme in der Industrie 4.0 Arbeitsrechtliche und beschäftigtendatenschutzrechtliche Fragestellungen in einem automatisierten Arbeitsumfeld - Hofmann, Kai (Der Elektronische Rechtsverkehr, 2021)
The work is dedicated to work in Industry 4.0, a development in which all real processes in the factory are to be digitally recorded and thus automated even more. This brings opportunities for employees, but also threatens de-skilling and comprehensive monitoring. In labour law, the legal binding force of the humane design of work and human-machine collaboration are therefore being examined. In privacy law the central question is to what extent the efficient organisation of work justifies intensive data processing. To this end, a new approach is presented, which is derived from the interplay of German and European fundamental rights and which differentiates between the two areas of law.